(untitled) (Bangladesh Journal of Zoology, 2015)
Social interactions of Hanuman langurs (Semnopithecus entellus) were studied from August, 2013 to July, 2014 at Keshabpur and Manirampur Upazila, Jessore, Bangladesh. The study was mainly based on direct field observations from dawn to dusk and data was collected through focal animal sampling in 10- minutes duration. During the study period seven groups of Hanuman langurs were found in urban and rural habitats. Eight behavioral activities like resting, feeding, grooming, moving, parental care, playing, submission and aggression were recorded. They interacted with each other through grooming, parental care, playing, submission and aggression. Social interactions varied in urban and rural habitats. Aggression was mostly observed in rural habitat and generally showed by the males. Adults were engaged in playing to encourage infants, juveniles and sub-adults. Significant seasonal variation of grooming was observed between age classes. Females were engaged more in grooming and parental care than males. Allomothering was also observed within a group. More submission was received by dominant males within a group. Langurs of focal groups spent 41.04% of their total activity budget in resting which was the highest activity followed by 33.75% in feeding, 11.73% in grooming, 4.87% in moving and 8.61% time for other activities. Bangladesh J. Zool. 42(2): 217-225, 2014